Perspectives for the international location of the steel industry - Frank Wolter (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1977)
Lasting steel crises in Western European and North American countries and increasing efforts of developing countries in establishing national steel industries are contrasting features of today's international steel scene. Has comparative advantage in steel production shifted from the former to the latter countries? Developing countries seem to think so. Their discontent with the structural changes in the world economy which have emerged in the aftermath of World War II have led to demands for a New International Economic Order whose core targets encompass the introduction of an integrated raw material program and the enlargement of the developing countries' share in world industrial production to 25 p.c. in 2000. To achieve the industrialization target, priority sectors, among which is the steel industry, have been selected. In the present analysis an attempt is made to identify the determinants and to trace the probable shifts of this industry's international location which are to be expected from an economic point of view.
Keywords: 330